The impact of privatisation on capital market development and individual share ownership - William L. Megginson; Maria K. Boutchkova (Fondazione Eni Enrico Mattei (FEEM), 2000)
This study has two objectives: to estimate the impact of share issue privatisations on the growth of world capital markets (especially stock markets), and to examine the effect privatisation has had on the pattern of share ownership by individuals and institutional investors. We begin by documenting the increasing importance of capital markets, and the declining role of commercial banks, in corporate financial systems around the world. We then show that privatisation programmes have had a dramatic impact both on the development of non-U.S. stock markets and on the participation of individual and institutional investors in those markets. Our research documents the following key points: (1) the fraction of total domestic credit provided by the banking sector, as a percent of GDP, remained virtually constant (125 percent) between 1990 and 1998 for the world as a whole, as well as for most major country groupings. (2) During that same time period, stock market capitalisation as a percent of GDP increased from 52 to 82 percent for the world as a whole, and from 56 to 95 percent for high income countries. Market capitalisation is now over 39 trillion, which almost certainly exceeds world capitalisation. (3) Share trading volume (value of shares traded) increased even more dramatically, from 29.0 percent of world GDP in 1980 to 79.3 percent in 1998, when it reached 22.9 trillion. (4) The total market value of privatised firms grew from less than 50 billion in 1983 to almost 2.5 trillion in 1999-roughly 10 percent of the world's aggregate market capitalisation, and 21 percent of the non-U.S. total. (5) Privatised firms are the most valuable companies in seven of the ten largest non-U.S. stock markets, including the four largest, as well as in most developing countries. (6) Share issue privatisations (SIPs) have transformed international equity issuance and investment banking practices. The 25 largest–and 35 of the 39 largest–common stock issues in history have all been privatisations, and governments have raised over 700 billion through some 750 SIPs since 1977–and over 1 trillion through all privatisation methods. (7) Academic research has now clearly established that, in most countries, SIP investors earn significantly positive excess (market-adjusted) returns on the shares they purchase–over both short and long term holding periods. (6) Privatisations have dramatically increased the number of shareholders in many countries. Almost two-thirds of the 54 non-U.S. firms (67 including US companies) with over 500,000 shareholders are privatised companies, and roughly a dozen SIPs have more than 1,000,000 initial shareholders. SIPs generally have a far larger number of stockholders than do capitalisation-matched private firms in the same country. (7) However, we also find that the extremely large numbers of shareholders created by many SIPs are not a stable ownership structure. For the 47 offers that initially yield over 250,000 shareholders, the total number of shareholders declines by one-third within five years.
Keywords: 330; Privatisierung; Börsengang; Finanzmarkt; Aktionäre; Institutioneller Investor; Welt